Educational assessment and professional performance: Relationship between academic performance and the practical professional examination - Gonzalo Armando Navarro-Armendáriz; Aziel Alejandro Peralta-Ramírez; Sayil Alejandra DeLaTorre-Othón; María Elena Reguera-Torres; Izabel Navyla Madrid-Moreno; Héctor Clemente Baltierra-Ochoa (Educación Médica, 2025)
Introduction: This study examines the relationship between academic performance (Kardex grades) and clinical competence, measured by the Practical Professional Examination (PPT), in medical graduates from the Universidad de Sonora. While academic grades are often used to predict clinical success, their correlation with clinical skills remains uncertain. Methods: An observational, retrospective analysis of 358 graduates (2019–2024) was conducted, assessing both final grades and PPT performance. Nine key clinical competencies, including diagnostic reasoning, physical examination, and patient communication, were evaluated. Spearman's correlation was used for non-normal distributions. Results: The mean Kardex grade was 92.76, and the mean PPT score was 87.72. Significant correlations were found between clinical competencies (e.g., differential diagnosis and physical examination) and PPT performance, with the strongest correlation in differential diagnosis (r = 0.777, p < 0.001). However, the correlation between Kardex grades and PPT performance was weak (r = 0.152, p = 0.004), suggesting that academic grades do not reliably predict clinical competence. Conclusion: Findings indicate that strong academic performance does not guarantee clinical skills. Essential competencies, such as diagnostic reasoning, are crucial in clinical assessments. Medical education should integrate theoretical knowledge with hands-on practice through strategies like problem-based learning (PBL) and Objective Structured Clinical Examinations (OSCE). While academic performance reflects theoretical knowledge, it is not a strong predictor of clinical competence. Enhancing the integration of theory and practice is essential to better prepare graduates for real-world clinical settings. Resumen: Introducción: Este estudio examina la relación entre el rendimiento académico (calificaciones Kardex) y la competencia clínica, medida a través del Examen Profesional Práctico (PPT), en egresados de Medicina de la Universidad de Sonora. Aunque las calificaciones académicas suelen utilizarse para predecir el éxito clínico, su correlación con las habilidades clínicas sigue siendo incierta. Métodos: Se realizó un análisis observacional y retrospectivo de 358 egresados (2019–2024), evaluando tanto las calificaciones finales como el desempeño en el PPT. Se evaluaron nueve competencias clínicas clave, incluyendo el razonamiento diagnóstico, el examen físico y la comunicación con el paciente. Se utilizó la correlación de Spearman para distribuciones no normales. Resultados: La calificación promedio del Kardex fue de 92.76, y la puntuación promedio del PPT fue de 87.72. Se encontraron correlaciones significativas entre las competencias clínicas (por ejemplo, diagnóstico diferencial y examen físico) y el desempeño en el PPT, siendo la correlación más fuerte en el diagnóstico diferencial (r = 0.777, p < 0.001). Sin embargo, la correlación entre las calificaciones del Kardex y el desempeño en el PPT fue débil (r = 0.152, p = 0.004), lo que sugiere que las calificaciones académicas no predicen de manera confiable la competencia clínica. Conclusión: Los resultados indican que un buen rendimiento académico no garantiza habilidades clínicas. Competencias esenciales, como el razonamiento diagnóstico, son cruciales en las evaluaciones clínicas. La educación médica debe integrar el conocimiento teórico con la práctica mediante estrategias como el aprendizaje basado en problemas (PBL) y los Exámenes Clínicos Estructurados Objetivos (OSCE). Aunque el rendimiento académico refleja el conocimiento teórico, no es un predictor fuerte de la competencia clínica. Mejorar la integración de la teoría y la práctica es esencial para preparar mejor a los egresados para los entornos clínicos del mundo real.